The studies of using composite material for temporary repair of shut-off valves on main oil pipelines - Yu. O. Filippov (Омский научный вестник)
The paper presents the results of studies of composite materials based on epoxy resins with different types of filling are considered. It is shown that a material with a metal filler has higher mechanical characteristics compared to a material filled with ceramics. The material retains high mechanical properties at low temperatures and after interaction with petroleum products. Hydraulic tests showed that the material with a ceramic filler withstood only on non-through defects. The metal-filled material has passed the tests for non-through defects and through defects at pressures up to 4,0 MPa. The material with a filler based on Fe and Cr powder can be used in pipeline construction for temporary repair of valves with non-through defects or through defects of valves operating up to 1,6 MPa.